Doris Lessing's The Grass is Singing: a Projection of Naturalism - Tiwari, Rajendra P (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
This article explores the demonstration of naturalism in Doris Lessing’s first tragic novel the Grass is Singing. It relates how the main characters in the novel are influenced by their instinct, their social and economic environment and how their failure or success depends on their adaptability and ability to compete in the struggle for survival. It is based on library study and textual analysis. Result shows that the central characters, Mary Turner and Moses, are the victims of heredity (sexual instinct) and environment (social, economic and political forces), and Dick Turner suffers the consequence of his environment and his failure to prove himself in the competition or struggle for survival. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10467 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 39-50